Combining Cellular Immunology With RNAseq to Identify Novel Chlamydia T-Cell Subset Signatures. (16th February 2022) - Johnson, Raymond M; Asashima, Hiromitsu; Mohanty, Subhasis; Shaw, Albert C
Abstract: Chlamydia trachomatis serovars A–L cause important diseases of the eyes and reproductive tract by infecting epithelium lining those organs. A major hurdle for vaccine trials is finding a surrogate biomarker for protective immunity. Investigational data argues for T-cell biomarker(s) reflecting mucosal adaption, cytokine polarization, B-cell help, antibacterial effector mechanisms, or some combination thereof. A human investigation and 2 mouse studies link IL-13 to protection from infection/immunopathology. We performed RNAseq on T cells resident in spleens and genital tracts of naturally immune mice. CD4 signatures were consistent with helper function that differed by site including a genital tract-specific Fgl2 signal. The genital tract CD8 signature featured IL-10 and promotion of healing/scarring with a unique transcription of granzyme A. The RNAseq data was used to refine previously published CD4γ13 and CD8γ13 transcriptomes derived from protective T-cell clones, potentially identifying practicable T-cell subset signatures for assessing Chlamydia vaccine candidates. Abstract : Comparing protective T-cell clone transcriptomes to the chlamydia immune genital tract transcriptome revealed unique mucosal immunobiology and components for putative protective T-cell signatures based on 9 genes for CD4 and 13 genes for CD8 T cells.